Grid Impact of Frequency Regulation Provided by V2Gs Aggregated at HV, MV, and LV Level - Marta Bernal-Sancho; Roberto Rocca; Gregorio Fernandez-Aznar; Maria Paz Comech; Noemi Galan-Hernandez (IEEE Access, 2023)
Vehicle-to-Grid chargers (V2Gs) are currently considered a key component for supporting future power systems in primary and especially secondary frequency regulation. Most of the research works conducted so far on this topic are based on a vehicle-centric perspective, whereas global approaches where the impact caused by fleets of V2Gs is studied from the perspective of an entire electric grid remain quite unexplored. In particular, the effects of aggregating different amounts of V2Gs from the HV, MV and LV subgrids to participate in frequency control represents a novel aspect to be investigated, which is expected to possess a strong potential for further improving the aggregation processes. To this end, this work presents a “global working framework” developed to evaluate the impact on an entire electric system of V2Gs participation in frequency regulation. A reality-based electric network is considered, where two HV, three MV and ten LV subgrids are interconnected. The effects of four different percentages of V2Gs aggregated from the HV, MV and LV subgrids are evaluated for two V2G installed capacities, 10 MW and 20 MW. Results are finally analyzed, including frequency vs time response, rate of change of frequency, grid losses, etc., and valuable knowledge, insights and guidelines are obtained for guiding future grid-level aggregation optimizations of V2Gs participation in frequency regulation.